2021
DOI: 10.1007/s00198-021-05947-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for multi-joint disease in patients with glucocorticoid-induced osteonecrosis

Abstract: Summary This study investigated risk factors for osteonecrosis involving multiple joints (MJON) among glucocorticoid-treated patients. The best predictor of MJON was cumulative oral glucocorticoid dose. Risk of MJON was 12-fold higher in patients who had a second risk factor for osteonecrosis. Further research is needed into strategies for prevention of MJON. Introduction Osteonecrosis (ON) is a debilitating musculoskeletal condition in which bone cell death can lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The administration of these drugs may increase the risk of ON by up to 20 times [ 5 ]. It was also found that steroid use in some conditions is associated with multifocal disease, mainly rheumatic diseases—including SLE, malignancies (such as acute lymphoblastic leukemia and non-Hodgkin lymphoma), and pulmonary disease [ 51 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of these drugs may increase the risk of ON by up to 20 times [ 5 ]. It was also found that steroid use in some conditions is associated with multifocal disease, mainly rheumatic diseases—including SLE, malignancies (such as acute lymphoblastic leukemia and non-Hodgkin lymphoma), and pulmonary disease [ 51 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Physiological levels of endogenous steroids are necessary for bone mass maintenance [ 50 , 59 ]. It is clear, however, that excess endogenous (as in the Cushing syndrome) and therapeutic steroids, as well as their deficiency (as seen in Addison’s syndrome), may seriously impact bone homeostasis [ 50 , 51 , 53 , 55 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore our study showed for the first time on an homogeneous population that children who received treatment against leukemia, presented with multifocal joint involvement (mainly weight-bearing joints) at ON diagnosis while in other systemic pathologies, such as sickle cell anemia, also known for the frequent occurrence of osteonecrosis, involvement is predominantly unifocal (80% of cases) 29 . This is probably due to corticosteroid therapy, since Kuhlen et al has shown it in adult population 30 and Krez et al also showed that a high cumulative dose of glucocorticoids was associated with a risk of multifocal disease in patients with different underlying conditions like systemic lupus erythematosus 31 .…”
Section: Discussionmentioning
confidence: 99%
“…As a progressive and degenerative disease, osteonecrosis of the femoral head (ONFH) can cause subchondral micro-fracture and subsequent femoral head collapse, eventually leading to hip joint dysfunction ( 1 2 ). ONFH usually affects young to middle-aged individuals and poses a huge socioeconomic burden.…”
Section: Introductionmentioning
confidence: 99%